2018
DOI: 10.1093/geronb/gby029
|View full text |Cite
|
Sign up to set email alerts
|

Early-Life Military Exposures and Functional Impairment Trajectories Among Older Male Veterans: The Buffering Effect of Psychological Resilience

Abstract: Our findings point to the importance of psychological resilience in later life, especially within the realm of traumas occurring in early life. We discuss implications for current military training programs, stressing the importance of research considering individual resources and processes that promote adaptation in the face of adverse life events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…Studies adopting the life-course perspective document the role of later life resources in buffering early life disadvantages and trauma (Landes et al 2014;Taylor et al 2019). Analyzing a dataset of 636 men from the Harvard Sample and Inner City Cohort of the 73-year longitudinal Study of Adult Development, Landes et al (2014) showed that midlife generativity, a desire to guide the future generation, moderates the negative impact of childhood adversity on later-life adjustments to aging.…”
Section: Key Research Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies adopting the life-course perspective document the role of later life resources in buffering early life disadvantages and trauma (Landes et al 2014;Taylor et al 2019). Analyzing a dataset of 636 men from the Harvard Sample and Inner City Cohort of the 73-year longitudinal Study of Adult Development, Landes et al (2014) showed that midlife generativity, a desire to guide the future generation, moderates the negative impact of childhood adversity on later-life adjustments to aging.…”
Section: Key Research Findingsmentioning
confidence: 99%
“…Childhood adversity does not have a long-term effect if one acquires generativity, an indicator of psychological development and resilience (Landes et al 2014) (see ▶ "Generativity and Adult Development"). Psychological resilience also helps veterans to suffer less from functional impairment resulting from early-life traumatic military exposures (Taylor et al 2019). Received support and neighborhood satisfaction as social resources ameliorate a negative association between adverse childhood experiences and adult well-being (Nurius et al 2015).…”
Section: Key Research Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Military stressors are associated with post-traumatic stress disorder and post-traumatic growth (Park et al, 2008), which suggest that some veterans can access or activate resources to cope with combat exposures, while others cannot. Recent studies find that negative consequences of traumas may be counteracted or mitigated by psychological resilience (Spiro et al, 2016; Taylor et al, 2019), an internal resource shaping the ways adversities experienced during young to mid-adulthood influence well-being over the life course (Smith & Hayslip, 2012). Exploring mental health outcomes attributed to DDW exposure, given a veteran’s potential for adaptive response, is necessary to better understand the processes placing veterans at increased risk.…”
mentioning
confidence: 99%
“…Combat exposure is associated with higher psychiatric and health-related problems, and treatment-related costs (Dohrenwend et al, 2006; Gade & Wenger, 2011; Price, Risk, Haden, Lewis, & Spitznagel, 2004; Richardson, Frueh, & Acierno, 2010; Toblin et al, 2012). These negative effects are thought to be driven substantially by specific traumas such as exposure to death or hazardous toxins that are often experienced during wartime combat (Taylor, Ureña, Carr, & Min, 2018). Studies now find that measuring these specific exposures is important in understanding the lasting burden of service for today’s older veterans, but often research includes only a marker of likely wartime service as a general proxy (Ureña, Taylor, & Kail, 2017).…”
mentioning
confidence: 99%